A dental adhesive with low oxygen inhibition
By adding tertiary amine compounds to dental adhesives, peroxygen radicals are consumed and polymerization is promoted, the problems of reducing bond strength and slippage caused by the oxygen-resisting polymerization layer are solved, and the low-oxygen polymerization resistance effect with high bond strength and durability is achieved.
Patent Information
- Application Number
- CN202410062644.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-16
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-01-16
AI Technical Summary
Existing dental adhesives tend to form oxygen-resistant polymerization layers in the presence of oxygen, resulting in a decrease in bonding strength and slippage during resin filling.
A dental adhesive for low oxygen poly-resistance is used. The adhesive contains matrix resin, filler, tertiary amine compounds and solvents. As an active hydrogen donor, the tertiary amine compounds can react with peroxy radicals, consume non-addition active peroxy radicals, promote polymerization reactions, and reduce the thickness of the oxygen poly-resistance layer.
It improves the bonding strength and durability of dental adhesives, reduces the thickness of the oxygen-resistant polymer layer, and avoids slippage during resin filling. It is suitable for the bonding surfaces of dental restorations of enamel, dentin and various materials.
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of dental restorative materials technology, and in particular to a low-oxygen polymerization-inhibiting dental adhesive. Background Technology
[0002] Polymers are high molecular weight compounds formed by a large number of monomer molecules linked by chemical bonds. When polymers undergo polymerization in the presence of oxygen, oxygen reacts with the active intermediates in the polymer, thereby initiating an oxygen inhibition effect. The oxygen inhibition effect refers to the phenomenon that, under certain conditions, oxygen affects the polymer, causing its polymerization rate to slow down or stop. Especially in free radical polymerization reactions, the oxygen inhibition effect is prevalent. The inhibition effect of oxygen molecules is mainly manifested in the following two aspects: (1) quenching excited-state photoinitiators and preventing the generation of active free radicals; (2) combining with active free radicals to form non-additional peroxy free radicals.
[0003] Currently, most general-purpose adhesives contain photoinitiators, and most initiation systems are free radical reactions. Furthermore, most photocuring processes are carried out in air; therefore, oxygen molecules have a significant inhibitory effect on free radical polymerization. Photocured or chemically cured dental composite resins form a soft, viscous surface layer after polymerization, commonly referred to as an oxygen inhibitor layer. Increased thickness of the oxygen inhibitor layer reduces the adhesive strength between composite resin layers. Additionally, an excessively thick oxygen inhibitor layer can cause "slippage" during composite resin filling, hindering direct resin restoration. These shortcomings are issues that those skilled in the art aim to overcome. Summary of the Invention
[0004] The purpose of this invention is to overcome the above-mentioned defects in the prior art. This invention provides a low-oxygen polymerization inhibitory dental adhesive, which has the advantages of high adhesive strength and high adhesive durability.
[0005] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0006] A low-oxygen polymerization-inhibiting dental adhesive, comprising the following components by weight percentage:
[0007] Matrix resin 20wt%~90wt%;
[0008] Filler content: 0 wt% to 15 wt%;
[0009] Tertiary amine compounds, 1 wt% to 5 wt%;
[0010] The matrix resin comprises a polymerizable resin monomer, a photopolymerization initiator, and a photopolymerization accelerator; the polymerizable resin monomer is a polymerizable acrylate monomer; and the total content of the photopolymerization initiator and the photopolymerization accelerator is less than 10 wt%.
[0011] Furthermore, the polymerizable acrylate monomer is any one or a mixture of hydrophilic acrylic resin, hydrophobic acrylic resin, and acidic acrylic resin.
[0012] Further, the photopolymerization initiator is any one or a mixture of α-diketone, ketal, thioxanthone, (bis)acylphosphine oxide, benzoin alkyl ether, benzoyldimethyl ketal, coumarin, diaryliodomonium hexafluorophosphate, triarylthionium hexafluorophosphate, triarylselenium hexafluorophosphate, camphorquinone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO);
[0013] The photopolymerization accelerator is any one or a mixture of ethyl 4-dimethylaminobenzoate, N,N-dimethylaminoethyl ester and dimethylaminoethyl methacrylate.
[0014] Furthermore, the matrix resin also includes a polymerization inhibitor; the content of the polymerization inhibitor is less than 2 wt%.
[0015] Preferably, the polymerization inhibitor is any one of 2,6-di-tert-butyl-p-cresol, p-hydroxyanisole, or a mixture thereof.
[0016] Furthermore, the packing material is an inorganic packing material, an organic packing material, or a mixture of inorganic and organic packing materials.
[0017] Preferably, the average particle size of the filler is 0.001 μm to 1 μm.
[0018] Further, the tertiary amine compound is any one of triethanolamine, triethylamine, triethanolamine phosphate, N-methyldiethanolamine, dodecylamine, dodecyltetradecylamine, hexadecylamine, hexadecyloctadecylamine, octadecylhexadecylamine, dioctadecylamine, N,N-dimethylaniline, N,N-diethylaniline, N,N-dimethyl-p-toluidine, N,N-dihydroxyethyl-p-toluidine, N-methyl-N-hydroxyethyl-p-toluidine, N,N,N',N'-tetramethylethylenediamine, N,N-dimethylethanolamine, N,N'-dimethylpiperazine, and N,N,N',N'-tetramethylurea.
[0019] Furthermore, it also includes a solvent for diluting the adhesive and improving the system stability of the adhesive; the content of the solvent is 5 wt% to 60 wt%.
[0020] Preferably, the solvent is any one or a mixture of ethanol, isopropanol, acetone, methanol, n-butanol, cyclohexane, methylcyclohexane, dichloromethane, trichloroethylene, chloroform, methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, diethylene glycol monobutyl ether, butyl acetate, methyl ethyl ketone, cyclohexanone, turpentine, tetrahydrofuran, and deionized water.
[0021] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0022] This invention discloses a low-oxygen-inhibiting dental adhesive. By adding tertiary amine compounds to the system, these compounds, acting as active hydrogen donors, react rapidly with peroxide free radicals, consuming the non-addition-reactive peroxide free radicals and releasing alkoxy and hydroxyl free radicals. These released alkoxy and hydroxyl free radicals can also initiate the polymerization reaction of polymerizable acrylate monomers in the dental adhesive, thereby increasing the polymerization rate, promoting the curing of the dental adhesive, and effectively reducing the thickness of the oxygen-inhibiting layer. The low-oxygen-inhibiting dental adhesive exhibits high bonding strength, good bonding durability, and a thinner oxygen-inhibiting layer, which helps avoid slippage during resin filling. It is suitable for pretreatment of bonding surfaces of enamel, dentin, and various dental restorations, enabling various direct and indirect restorative procedures in oral restoration. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0024] This invention discloses a low-oxygen polymerization-inhibiting dental adhesive, comprising the following components: a matrix resin, a filler, a tertiary amine compound, and a solvent. The dental adhesive exhibits high bond strength, high bond durability, and a low-oxygen polymerization-inhibiting effect. It can be used for the pretreatment of bonding surfaces of enamel, dentin, and various dental restorations, enabling various direct and indirect restorative procedures in the oral restoration process.
[0025] The matrix resin accounts for 20 wt% to 90 wt% of the total system; for example, the matrix resin content may be, but is not limited to, 20 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 80 wt%, and 90 wt%. The matrix resin includes polymerizable resin monomers, photopolymerization initiators, photopolymerization accelerators, and polymerization inhibitors.
[0026] The polymerizable resin monomer is a polymerizable acrylate monomer; the polymerizable acrylate monomer can undergo a polymerization reaction under the action of a photopolymerization initiator and a photopolymerization accelerator. The polymerizable acrylate monomer is any one or more mixtures of hydrophilic acrylic resins, hydrophobic acrylic resins, and acidic acrylic resins. Hydrophilic acrylic resins include, but are not limited to, the following resins: hydroxyethyl methacrylate (HEMA), hydroxypropyl methacrylate (HPMA), glyceryl dimethacrylate (GDMA), glyceryl monomethacrylate (GMMA), 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxybutyl acrylate, 2-hydroxy-3-phenoxypropyl acrylate, 4-hydroxybutyl acrylate, or propylene glycol mono-methacrylate.
[0027] Hydrophobic acrylic resins include, but are not limited to, the following resins: dimethacrylate polyurethane (UDMA), diurea dimethacrylate (DUDMA), bisphenol A-dimethacrylate polyoxyethylene ether (EBPADMA), bisphenol A-dimethacrylate glycidyl ester (Bis-GMA), triethylene glycol dimethacrylate (TEGDMA), methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, cyclohexyl methacrylate, ethoxydiethylene glycol methacrylate, methoxytriethylene glycol methacrylate, phenoxyethyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 2-hydroxyethyl methacrylate. Hydroxy-3-phenoxypropyl ester, 4-hydroxybutyl methacrylate, 1,4-cyclohexanediethanol monomethacrylate, methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, hexyl acrylate, cyclohexyl acrylate, ethoxydiethylene glycol acrylate, methoxytriethylene glycol acrylate, phenoxyethyl acrylate, 1,4-butanediol di(meth)acrylate dodecanediol, di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, trimethylolpropane mono(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate (TMPTMA), pentaerythritol mono(meth)acrylate, pentaerythritol bis(meth)acrylate, or pentaerythritol tri(meth)acrylate.
[0028] Acidic acrylic resins include, but are not limited to, the following resins: 10-methacryloyloxydecyl phosphate (10-MDP), alkyl acrylate phosphates, glycerol dimethacrylate phosphate (Bis-GDMAP), 2-hydroxyethyl methacrylate phosphate, di(methacryloyloxyethyl) hydrogen phosphate, ethylene glycol methacrylate phosphate, methacryloyloxyethyl phosphate, methacryloyloxyethyl trimellitic anhydride, 4-[2-[(meth)acryloyloxy]ethoxycarbonyl]phthalic acid, acrylic acid-methylene succinic acid copolymer, mercaptomethyl methacrylate, 5-(meth)acryloyloxypentyl-3-phosphonopropionate or ethylene glycol di(3-mercaptopropionate) and trimethylolpropane tri(3-mercaptopropionate).
[0029] The total content of photopolymerization initiator and photopolymerization accelerator is less than 10 wt%; preferably, the total content of photopolymerization initiator and photopolymerization accelerator accounts for 2 wt% to 6 wt% of the entire system. As an example, the total content of photopolymerization initiator and photopolymerization accelerator may be, but is not limited to, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.5 wt%, 9 wt%, 9.5 wt%, and 10 wt%.
[0030] Photopolymerization initiators initiate the polymerization reaction of polymerizable acrylate monomers by absorbing light energy. These initiators control the setting time and hardening degree of the dental adhesive, ensuring good flowability and adaptability during bonding. The photopolymerization initiator is any one or a mixture of α-diketones, ketals, thioxanthones, (bis)acylphosphine oxides, benzoin alkyl ethers, benzoin dimethyl ketals, coumarins, diaryliodomonium hexafluorophosphate, triarylthionium hexafluorophosphate, triarylselenium hexafluorophosphate, camphorquinone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO); preferably, camphorquinone is the photopolymerization initiator. Photopolymerization accelerators assist photopolymerization initiators, enhancing their ability to absorb light energy, thereby increasing the polymerization rate and efficiency of polymerizable acrylate monomers. The photopolymerization accelerator is any one or a mixture of ethyl 4-dimethylaminobenzoate, N,N-dimethylaminoethyl ester and dimethylaminoethyl methacrylate.
[0031] The content of the polymerization inhibitor is less than 2 wt%; as an example, the content of the polymerization inhibitor may be, but is not limited to, 0 wt%, 0.2 wt%, 0.4 wt%, 0.6 wt%, 0.8 wt%, 1 wt%, 1.2 wt%, 1.4 wt%, 1.6 wt%, 1.8 wt%, or 2 wt%. The polymerization inhibitor is any one of 2,6-di-tert-butyl-p-cresol and p-hydroxyanisole, or a mixture thereof. The polymerization inhibitor is used to control the polymerization rate of polymerizable acrylate monomers, preventing the photopolymerization initiator from initiating the polymerization reaction too quickly, thus ensuring that the dentist has sufficient time to adapt to and shape the dental adhesive when using light-cured dental adhesives.
[0032] The filler content accounts for 0 wt% to 15 wt% of the total system; preferably, the filler content accounts for 1 wt% to 8 wt% of the total system. As an example, the filler content may be, but is not limited to, 0 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, and 15 wt%. The filler in the dental adhesive is used to improve the handling properties of the material and enhance the mechanical strength and adhesion of the dental adhesive after curing.
[0033] Specifically, the packing material can be any one of inorganic packing material, organic packing material, or a mixture of inorganic and organic packing material. The average particle size of the packing material is 0.001 μm to 1 μm; preferably, the average particle size of the packing material is 0.001 μm to 0.1 μm. As an example, the average particle size of the packing material can be, but is not limited to, 0.001 μm, 0.003 μm, 0.005 μm, 0.007 μm, 0.009 μm, 0.01 μm, 0.03 μm, 0.05 μm, 0.07 μm, 0.09 μm, 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, or 1 μm.
[0034] Inorganic fillers possess high hardness, strength, and durability, providing excellent optical properties and color stability, and are not easily discolored or faded by external environmental influences. Inorganic fillers can be silica-based fillers, glass-based fillers, or other commonly used dental inorganic fillers. Silica-based fillers are selected from amorphous silica powder, spherical silica powder, kaolin, and other silica-based minerals; commercially available ultrafine silica particles with a primary particle size of 0.001μm to 0.1μm include OX50, A200, A380, R974, R972, R711, R709, H30, H20, T30, T40, and similar specifications of particulate silica and fumed silica. Glass-based fillers are selected from barium glass, lanthanum glass, strontium glass, sodium glass, lithium borosilicate glass, zinc glass, fluoroaluminosilicate glass, borosilicate glass, and bio-glass. Other commonly used dental inorganic fillers are selected from zirconium oxide, hydroxyapatite, alumina, titanium dioxide, sodium fluoride, potassium fluoride, strontium fluoride, ytterbium trifluoride, and iron oxide. Organic fillers have good processability and flowability, and are used to fill small defects or weakly bonded tooth areas. A mixture of inorganic and organic fillers, prepared by blending inorganic and organic fillers in a certain proportion, possesses the characteristics of both inorganic and organic fillers. Preferably, the filler is silanized fumed silica; silanized fumed silica can enhance the mechanical properties and durability of the dental adhesive and improve its compatibility.
[0035] The content of tertiary amine compounds accounts for 1 wt% to 5 wt% of the total system; as an example, the content of tertiary amine compounds may be, but is not limited to, 1 wt%, 1.2 wt%, 1.4 wt%, 1.6 wt%, 1.8 wt%, 2 wt%, 2.2 wt%, 2.4 wt%, 2.6 wt%, 2.8 wt%, 3 wt%, 3.2 wt%, 3.4 wt%, 3.6 wt%, 3.8 wt%, 4 wt%, 4.2 wt%, 4.4 wt%, 4.6 wt%, 4.8 wt%, and 5 wt%.
[0036] Tertiary amine compounds can effectively reduce the oxygen inhibition layer and prevent slippage during resin filling. The main principle is that tertiary amine compounds, as active hydrogen donors, can rapidly react with peroxide free radicals generated during polymerization, regenerating these active free radicals. Specifically, tertiary amine compounds react with peroxide free radicals, which abstract hydrogen to generate alkyl hydrogen peroxide; alkyl hydrogen peroxide can further generate alkoxy radicals and hydroxyl radicals. The specific reaction is as follows:
[0037] ROO·+R'─CH2─NR2→ROOH+R'─C·H─NR2ROOH
[0038] ROOH→RO·+·OH
[0039] In addition to consuming peroxide radicals, the reaction of tertiary amine compounds with peroxide radicals releases alkoxy and hydroxyl radicals, which can then initiate the polymerization of polymerizable acrylate monomers in the dental adhesive, increasing the polymerization rate and promoting the curing of the dental adhesive. Therefore, tertiary amine compounds can also act as co-initiators in the dental adhesive, promoting its curing and effectively reducing the thickness of the oxygen-inhibiting layer.
[0040] The tertiary amine compounds are any one of triethanolamine, triethylamine, triethanolamine phosphate, N-methyldiethanolamine, dodecylamine, dodecyltetradecylamine, hexadecylamine, hexadecyloctadecylamine, octadecylhexadecylamine, dioctadecylamine, N,N-dimethylaniline, N,N-diethylaniline, N,N-dimethyl-p-toluidine, N,N-dihydroxyethyl-p-toluidine, N-methyl-N-hydroxyethyl-p-toluidine, N,N,N',N'-tetramethylethylenediamine, N,N-dimethylethanolamine, N,N'-dimethylpiperazine, and N,N,N',N'-tetramethylurea.
[0041] The solvent content is 5 wt% to 60 wt% of the total system; preferably, the solvent content is 5 wt% to 15 wt% of the total system. As examples, the solvent content may be, but is not limited to, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, and 60 wt%. The solvent is used to dilute the adhesive, improve the stability of the dental adhesive system, and improve the permeability of the dental adhesive during use. The solvent is any one or a mixture of ethanol, isopropanol, acetone, methanol, n-butanol, cyclohexane, methylcyclohexane, dichloromethane, trichloroethylene, chloroform, methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, diethylene glycol monobutyl ether, butyl acetate, methyl ethyl ketone, cyclohexanone, turpentine, tetrahydrofuran, and deionized water.
[0042] To better illustrate the purpose, technical solution, and beneficial effects of this invention, the following description, in conjunction with embodiments, will further explain the invention. It should be noted that the methods described below are further explanations of the invention and should not be construed as limiting it.
[0043] Example 1
[0044] This embodiment provides a low-oxygen polymerization-inhibiting dental adhesive, comprising the following raw materials in parts by weight: 10 parts of trimethylolpropane trimethacrylate, 5 parts of glycerol dimethacrylate, 16 parts of bisphenol A-dimethacrylate glycidyl acrylate, 25 parts of hydroxyethyl methacrylate, 10 parts of 10-methacryloyloxydecyl phosphate, 0.5 parts of camphorquinone, 0.3 parts of ethyl 4-dimethylaminobenzoate, 0.05 parts of 2,6-di-tert-butyl-p-cresol, 0.05 parts of p-hydroxyanisole, 2.4 parts of fumed silica, 30 parts of anhydrous ethanol, and 2 parts of triethanolamine;
[0045] Weigh each raw material according to the above-mentioned weight proportions; stir the resin, additives, fillers, solvents and other components separately, and after uniformly mixing the components, a low-oxygen-inhibiting dental adhesive is obtained.
[0046] Example 2
[0047] This embodiment provides a low-oxygen polymerization-inhibiting dental adhesive, comprising the following raw materials in parts by weight: 10 parts of trimethylolpropane trimethacrylate, 5 parts of glycerol dimethacrylate, 16 parts of bisphenol A-dimethacrylate glycidyl acrylate, 25 parts of hydroxyethyl methacrylate, 10 parts of 10-methacryloyloxydecyl phosphate, 0.5 parts of camphorquinone, 0.3 parts of ethyl 4-dimethylaminobenzoate, 0.05 parts of 2,6-di-tert-butyl-p-cresol, 0.05 parts of p-hydroxyanisole, 2.4 parts of fumed silica, 30 parts of anhydrous ethanol, and 2 parts of triethylamine;
[0048] Weigh each raw material according to the above-mentioned weight proportions; stir the resin, additives, fillers, solvents and other components separately, and after uniformly mixing the components, a low-oxygen-inhibiting dental adhesive is obtained.
[0049] Comparative Example
[0050] This comparative example provides an adhesive comprising the following raw materials in parts by weight: 10 parts trimethylolpropane trimethacrylate, 5 parts glycerol dimethacrylate, 16 parts bisphenol A-dimethacrylate glycidyl acrylate, 25 parts hydroxyethyl methacrylate, 10 parts 10-methacryloyloxydecyl phosphate, 0.5 parts camphorquinone, 0.3 parts ethyl 4-dimethylaminobenzoate, 0.05 parts 2,6-di-tert-butyl-p-cresol, 0.05 parts p-hydroxyanisole, 2.4 parts fumed silica, and 30 parts anhydrous ethanol;
[0051] Weigh each raw material according to the above-mentioned weight proportions; stir the resin, additives, fillers, solvents and other components separately, and after the components are evenly mixed, the adhesive is obtained.
[0052] In summary, the composition and dosage of the low-oxygen polymerization-inhibiting dental adhesives prepared in Examples 1-2 and the adhesives prepared in the comparative example are shown in Table 1 below.
[0053] Table 1: Component Table
[0054] Comparative Example Example 1 Example 2 10-MDP 10 10 10 HEMA 25 25 25 GDMA 5 5 5 Bis-GMA 16 16 16 TMPTMA 10 10 10 CQ 0.5 0.5 0.5 EDB 1 1 1 BHT 0.05 0.05 0.05 MEHQ 0.05 0.05 0.05 R974 2.4 2.4 2.4 Anhydrous ethanol 30 30 30 P1 - 2 — P2 - - 2
[0055] Note that the Chinese names of the abbreviations used in Table 1 are as follows:
[0056] <Polymerizable acrylic resin>
[0057] 10-MDP: 10-Methacryloxydecyl phosphate
[0058] HEMA: Hydroxyethyl methacrylate
[0059] Bis-GMA: Bisphenol A-dimethacrylate glycidyl ester
[0060] TMPTMA: Trimethylolpropane tri(meth)acrylate
[0061] GDMA: Glyceryl dimethacrylate
[0062] <Inorganic packing>
[0063] R974: Fumed silica
[0064] <Cure-initiating system>
[0065] CQ: Camphorquinone (photopolymerization initiator)
[0066] EDB: Ethyl 4-dimethylaminobenzoate (photopolymerization accelerator)
[0067] Tertiary amines
[0068] P1: Triethanolamine
[0069] P2: Triethylamine
[0070] <Other>
[0071] BHT: 2,6-Di-tert-butyl-p-cresol (polymerization inhibitor)
[0072] MEHQ: p-Hydroxyanisole (polymerization inhibitor)
[0073] Product performance testing
[0074] 1. Bond strength and bond durability are important indicators for evaluating the mechanical properties of an adhesive system. Higher bond strength and bond durability provide a foundation for good bonding results. The low-oxygen-inhibiting dental adhesives prepared in Examples 1-2 and the adhesives prepared in the comparative examples were tested for bond strength (enamel bond strength and dentin bond strength), bond durability (enamel bond strength and dentin bond strength), and uncured layer thickness (i.e., oxygen-inhibiting layer) using YY 1042-2011, YY T0519-2009, and YY 0622-2008 dental resin-based fissure sealants as reference standards. The test results are shown in Table 2 below.
[0075] Table 2 Test Results of Bond Strength, Bond Durability, and Uncured Layer Thickness
[0076]
[0077]
[0078] As shown in Table 2, under the same conditions, the thickness of the uncured layer of the low-oxygen polymerization-inhibiting dental adhesives prepared in Examples 1 and 2 is smaller than that of the adhesive prepared in the comparative example; at the same time, the bond strength and bond durability meet the standard requirements without significant reduction. Therefore, the above tests demonstrate that adding tertiary amine compounds can reduce the thickness of the uncured layer, effectively improve the curing effect of the dental adhesive, and thus achieve ideal restorative results in clinical bonding and restoration fillings.
[0079] 2. The low-oxygen polymerization-inhibiting dental adhesive prepared in Example 1 and two similar commercially available products (commercially available product 1 and commercially available product 2) were compared, and the uncured layer thickness of the three was compared. The test results are shown in Table 3 below.
[0080] Table 3 Test results of bond strength, bond durability and uncured layer thickness
[0081]
[0082] As shown in Table 3, the thickness of the uncured layer of the low-oxygen polymerization-inhibiting dental adhesive prepared in Example 1 is less than that of commercially available products 1 and 2. Furthermore, the bonding strength and bonding durability of the low-oxygen polymerization-inhibiting dental adhesive prepared in Example 1 under self-curing conditions are essentially at the same level as those of commercially available products 1 and 2. Therefore, the above tests demonstrate that the dental adhesive provided by this invention has the advantage of a thinner uncured layer compared to commercially available products.
[0083] The dental adhesive provided by this invention has high bonding strength, good bonding durability, and a thin oxygen inhibition layer, which helps to avoid slippage during resin filling. It is suitable for the pretreatment of bonding surfaces of dental restorations made of enamel, dentin, and various other materials, and can complete various direct and indirect restorative operations in the oral restoration process.
[0084] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A low oxygen inhibited dental adhesive, characterized in that: The invention is composed of the following raw materials in parts by weight: 10 parts of trimethylolpropane trimethacrylate, 5 parts of glycerol dimethacrylate, 16 parts of bisphenol A-glycidyl dimethacrylate, 25 parts of hydroxyethyl methacrylate, 10 parts of 10-methacryloyloxydecyl phosphate, 0.5 parts of camphorquinone, 0.3 parts of ethyl 4-dimethylaminobenzoate, 0.05 parts of 2,6-di-tert-butyl-p-cresol, 0.05 parts of p-hydroxyanisole, 2.4 parts of fumed silica, 30 parts of anhydrous ethanol and 2 parts of tertiary amine compounds, wherein the tertiary amine compounds are triethanolamine or triethylamine.
Citation Information
Patent Citations
One-pack type adhesive composition for dental use
CN1917845A